Three evil wishes - Stine R.L; Stine, R. L.; Copyright Paperback Collection (Library of Congress) (New York : Pocket Books, 1997)
Hannah won't open the bottle she found in Fear Lake, not after she reads the warning label. But her younger brother, Jesse, pulls off the cork and lets loose a genie who has been trapped inside for 100 years and who is not happy about it.
"A Parachute Press book."
"A Minstrel book."
Keywords: Horror tales